2011
DOI: 10.1021/ac102424h
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Process of Lead Chromate in Paintings by Vincent van Gogh Studied by Means of Synchrotron X-ray Spectromicroscopy and Related Methods. 1. Artificially Aged Model Samples

Abstract: On several paintings by artists of the end of the 19th century and the beginning of the 20th Century a darkening of the original yellow areas, painted with the chrome yellow pigment (PbCrO(4), PbCrO(4)·xPbSO(4), or PbCrO(4)·xPbO) is observed. The most famous of these are the various Sunflowers paintings Vincent van Gogh made during his career. In the first part of this work, we attempt to elucidate the degradation process of chrome yellow by studying artificially aged model samples. In view of the very thin (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
154
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(169 citation statements)
references
References 41 publications
10
154
0
5
Order By: Relevance
“…Several examples of the discoloration of synthetic yellow pigments from the turn of the twentieth century (e.g. zinc yellow (K 2 OÁ4ZnCrO 4 Á3H 2 O) [1], chrome yellow (PbCrO 4 ) [2][3][4][5][6], and cadmium yellow (CdS) [7,8]) have been recently reported.…”
Section: Introductionmentioning
confidence: 99%
“…Several examples of the discoloration of synthetic yellow pigments from the turn of the twentieth century (e.g. zinc yellow (K 2 OÁ4ZnCrO 4 Á3H 2 O) [1], chrome yellow (PbCrO 4 ) [2][3][4][5][6], and cadmium yellow (CdS) [7,8]) have been recently reported.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Chrome yellows are often encountered in paintings from the end of 19th Century, such as in Falling leaves (Les Alyscamps) by van Gogh (1853-1890), [2,3] but also in works by Seurat (1859-1891) [4] and others. They are known to be sensitive towards darkening when exposed to sunlight.…”
mentioning
confidence: 99%
“…Understanding the alteration processes of the pigments is of key importance both to (re)assess/ optimize the conditions in which works of art are stored and/ or to allow selection of appropriate restoration treatments. [1,7] In previous studies, artificial aging of lead chromate based compounds were performed through (a combination of) UV/ Vis light, heat, contaminants, [5,[8][9][10] and atmospheric gases (such as SO 2 [10] or H 2 S [11] ). By means of X-ray absorption nearedge structure (XANES) measurements at the micrometer scale, we previously demonstrated that the alteration of chromium yellow is associated with the reduction of the original Cr VI centers to Cr III .…”
mentioning
confidence: 99%
See 2 more Smart Citations